Terapi Musik pada Gangguan Tidur Insomnia - Reisani Hardi Kamagi; Junaiti Sahar (Journal of Telenursing (JOTING), 2021)
This study aims to identify music therapy in insomnia sleep disorders. The research design used is a systematic review through Scopus, ScienceDirect, ClinicalKey and Wiley Online with the keywords Sleep disorder, Insomnia, Sleep quality and Music therapy from 2017-2021. The results showed that music therapy with a tempo of 60-80 beats that was listened to 30-60 minutes before going to bed for approximately 1 to 2 weeks improved sleep quality by positively affecting PSQI scores. In conclusion, music therapy with soothing tones can reduce insomnia symptoms. Keywords: Sleep Disorders, Insomnia, Sleep Quality, Music Therapy